The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1590/s0034-89102000000700005
|View full text |Cite
|
Sign up to set email alerts
|

Evolução da assistência materno-infantil na cidade de São Paulo (1984-1996)

Abstract: Resumo ObjetivoDescrever a evolução da assistência materno-infantil, com base nas informações extraídas de dois inquéritos domiciliares realizados nos anos de 1984/85 e de 1995/ 96, na cidade de São Paulo, SP. Métodos Foram estudadas amostras probabilísticas da população entre zero e 59 meses de idade: 1.016 crianças em 1984/85 e 1.280 crianças em 1995/96. Três componentes da assistência materno-infantil foram investigados: assistência pré-natal, assistência ao parto e ao recém-nascido e assistência de puericu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1
36

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 12 publications
0
10
1
36
Order By: Relevance
“…An association between low maternal education and inadequate prenatal care has been found in Brazilian studies. 12,13 Previous fetal loss is a well described 8 risk factor; however, in the study data, previous fetal death did not increase risk significantly (OR=1.3; 95% CI: 0.45; 3.5); but the subsample size was small (eight cases and 12 controls) with wide confidence intervals. Previous low birth weight infant was the only aspect of reproductive history associated with risk of antepartum fetal death.…”
Section: Discussioncontrasting
confidence: 60%
“…An association between low maternal education and inadequate prenatal care has been found in Brazilian studies. 12,13 Previous fetal loss is a well described 8 risk factor; however, in the study data, previous fetal death did not increase risk significantly (OR=1.3; 95% CI: 0.45; 3.5); but the subsample size was small (eight cases and 12 controls) with wide confidence intervals. Previous low birth weight infant was the only aspect of reproductive history associated with risk of antepartum fetal death.…”
Section: Discussioncontrasting
confidence: 60%
“…Other improvements in infant health indicators, such as increases in the duration of breastfeeding and in the percentage of children receiving immunization and improvements in antenatal care, are likely to have contributed towards the advancement of infant health as a whole. 2,10 Reductions in fecundity -and consequent reductions in the number of births -may also have contributed towards the decrease in IMR. 9 Generally speaking, the analysis of IMRs in the São Paulo Metropolitan Area showed that public policies aimed at improving basic sanitary conditions have been effective in reducing post-neonatal mortality, which is due mainly to diseases related to the environment in which the child lives.…”
Section: Discussionmentioning
confidence: 99%
“…This indicator is closely connected with preterm birth, that is, the lower the gestational age, the lower the weight at birth. Compared to other countries such as Sweden and Norway, mean weight at birth is 3500g and the proportion of low weight is not more than 5% (18) .…”
Section: Discussionmentioning
confidence: 73%
“…Availability and quality of care offered by health services to pregnant women, newborn and children condition evolvement of health during childhood (18) . Relationship between the lack of or poor prenatal care and intrauterine growth retard, preterm birth, and morbidity and mortality during childhood has already been demonstrated (20) , it is essential to pay attention to these indicators.…”
Section: Discussionmentioning
confidence: 99%